Quantum-Scale Friction at Solid–Liquid Interface: Simulation, Detection Techniques, Mechanisms, and Emerging Applications - Han, Yishu; Zhang, Rui; Liu, Dameng; Luo, Jianbin (Nano-Micro Letters, 2026)
Solid–liquid interfaces are ubiquitous in nature and engineering, and their frictional behavior remains a key factor limiting performance gains in surface engineering. However, conventional tribology has largely focused on the effect of macroscopic variables such as surface topography, which do not account for the microscopic essence of ultra-low-friction phenomena at the nanoscale. Recently, the role of quantum-scale excitations, such as electrons and phonons, in micro-/nanoscale solid–liquid friction has been increasingly emphasized. By using in situ detection techniques such as terahertz time-domain spectroscopy and non-contact atomic force microscopy, the quantum-scale friction has been observed. Its essence stems from the energy and momentum transfer induced by fluctuations in liquid charge density or electron or phonon excitations within solids. However, limited capabilities in simultaneously probing multiple physical quantities at sub-nanometer and femtosecond resolutions hinder a comprehensive understanding of the quantum origins and applications of solid–liquid interfacial friction. This review synthesizes the cutting-edge theories and experimental advances in quantum-scale solid–liquid friction and proposes a potential breakthrough path based on deep integration of simulation and experiment to address core gaps, including incomplete theoretical frameworks and constrained detection capabilities. Despite multidimensional challenges, quantum-scale friction research demonstrates substantial potential for transformative technologies, such as low-power nanofluidic devices, high-efficiency energy storage, intelligent drug delivery, and super-lubrication materials, underscoring its significance for the convergence of interfacial science, quantum mechanics, and micro/nanofluidics. Highlights: 1 Reveals the quantum origin of solid liquid friction, governed by electron transfer, electron excitation, and electron-phonon coupling at interfaces. 2 Summarizes emerging characterization techniques and multiscale simulations that uncover quantum scale friction mechanisms beyond classical tribology. 3 Demonstrates the potential transformative applications of quantum scale interfacial friction in nano fluidics, energy harvesting, smart biomedical systems, and super lubrication.